The Role of Customer Satisfaction as Mediating the Influence of Brand Communication, Brand Evidence, and Gamification on Customer Loyalty: Case of Starbucks Store Manado Consumers - Rudy S. Wenas; Richo E. Suratman (AIBPM Publisher, 2018)
Customer satisfaction with consumed goods becomes a benchmark for product performance and the totality of marketer's performance. The degree of customer satisfaction is relative, depending on how much benefit and pleasure is received so that the customer will buy back even become loyal. Various ways can be done, but of course the tips done by marketers through brand communication, own brand as proof, and digital-based integrated marketing communications that are gamification are important things that can be considered. This study aims to examine and explain: the influence of brand communication, brand evidence, and gamification on customer satisfaction; the influence of brand communication, brand evidence, and gamification on customer loyalty; and customer satisfaction as mediating these three variables towards customer loyalty. Conducted on 100 respondents of Starbucks consumers who downloaded this international network application which was determined based on the purposive sampling method and by using the path analysis method. It is found that customer satisfaction is not a mediator of customer loyalty and so the brand communication is not influential. Meanwhile, brand evidence and gamification are factors that have a positive and significant effect on customer loyalty. The findings of this study explain that brand names, prices, services, and product interactions through digital-based integrated marketing communications play a role in determining customer loyalty especially for international stores such as Starbucks. Keywords: Customer Satisfaction, brand communication, gamification, customer loyalty